PRODUKSI PAKCOY DI LAHAN KERING MELALUI BUDIDAYA VERTIKULTUR PADA PUPUK N DENGAN MEDIA TANAM DAN INTERVAL BARIS YANG BERBEDA - Bano, Natalia Kresensia; Tobing, Wilda Lumban; Tefa, Azor Yulianus; Ndua, Natalia Desy Djata (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
This study aims to examine the production of bok choy in dry land due to differences in N fertilizer with planting media and row intervals through vertical fertigation cultivation. This study used a Split Plot Design with two factors, namely fertilizer with media and planting rows. The main plot was a combination of fertilizer and media consisting of: urea 1 g/L + POC 40 mL/L + BPN 10 mL/L with a planting medium of 50% soil: biochar - compost 50%; urea 0.5 g/L + POC 20 mL/L + BPN 5 mL/L with a planting medium of 50% soil: biochar - compost 50%; urea 1 g/L + POC 40 mL/L + BPN 10 mL/L with a planting medium of 25% soil: biochar - compost 75%; Urea 0.5 g/L + 20 mL/L Organic Fertilizer (POC) + 5 mL/L Organic Plant Growth Regulator (BPN) with a growing medium of 25% soil: biochar - 75% compost. The planting rows consisted of the first planting row, the second planting row, and the third planting row. The results showed that different N fertilizers, planting medium, and row intervals increased bok choy production in dryland, with the best results being achieved with urea 1 g/L + 40 mL/L Organic Fertilizer (POC) + 10 mL/L Organic Plant Growth Regulator (BPN) and 25% soil + 75% biochar - compost in the third row.